Improvement of the Corrosion Resistance of Carbon Steel by Plasma Deposited Thin Films - Rangel, Rita C.C.; Pompeu, Tagliani C.; Jr., José Luiz S. Barros; Antonio, César A.; Santos, Nazir M.; Pelici, Bianca O.; Freire, Célia M.A.; Cruz, Nilson C.; Range, Elidiane C. (IntechOpen, 2012)
None